Collaboration between meteorology and public health: Predicting the dengue epidemic in Guangzhou, China, by meteorological parameters - Chen, Jing; Ding, Rui-Lian; Liu, Kang-Kang; Xiao, Hui; Hu, Gang; Xiao, Xiang; Yue, Qian; Lu, Jia-Hai; Han, Yan; Bu, Jin; Dong, Guang-Hui; Lin, Yu (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Dengue has become an increasing public health threat around the world, and climate conditions have been identified as important factors affecting the transmission of dengue, so this study was aimed to establish a prediction model of dengue epidemic by meteorological methods. Methods: The dengue case information and meteorological data were collected from Guangdong Provincial Center for Disease Prevention and Control and Guangdong Meteorological Bureau, respectively. We used spatiotemporal analysis to characterize dengue epidemics. Spearman correlation analysis was used to analyze the correlation between lagged meteorological factors and dengue fever cases, and determine the maximum lagged correlation coefficient of different meteorological factors. And then Generalized Additive Models (GAMs) were used to analyze the non-linear influence of lagged meteorological factors on local dengue cases, and to predict the number of local dengue cases under different weather conditions. Results: We descripted the temporal and spatial distribution characteristics of dengue fever cases, and found that sporadic single or a small number of imported cases had a very slight influence on the dengue epidemic around. We further created a forecast model based on the comprehensive consideration of influence of lagged 42-days meteorological factors on local dengue cases, and the results showed that the forecast model has a forecast effect of 98.8%, which was verified by the actual incidence of dengue from 2005 to 2016 in Guangzhou. Conclusion: A forecast model for dengue epidemic was established with good forecast effects, and may have a potential application in global dengue endemic areas after modification according to local meteorological conditions. High attention should be paid on the sites with concentrated dengue patients for control of disease epidemic.